The Antidepressant Effect of Ketamine Is Dampened by Concomitant Benzodiazepine Medication - Andrashko, Veronika; Novak, Tomas; Brunovsky, Martin; Klirova, Monika; Sos, Peter; Horacek, Jiri (Frontiers in Psychiatry, 2020)
The rapid antidepressant effect of ketamine has become a breakthrough in the research and treatment of depression. Although predictive and modulating factors of the response to ketamine are broadly studied, little is known about optimal concurrent medication protocols. Concerning gamma-aminobutyric acid neurotransmission being a shared target for both ketamine and benzodiazepines (BZD), we evaluated the influence of BZD on the antidepressant effect of a single ketamine infusion in depressed patients. Data from 47 patients (27 females) with major depression (MADRS ≥ 20, ≥ 1 prior non-response to antidepressant treatment in current episode) who participated in two previous studies (EudraCT Number: 2009-010625-39 and 2013-000952-17) entered the analysis. All of the subjects were given an infusion of a subanaesthetic dose of racemic ketamine (0.54 mg per kg) as an add-on medication to ongoing antidepressive treatment. Thirteen patients (28%) reached ≥ 50% reduction in MADRS within one week after ketamine administration. Nineteen (40%) patients took concomitant benzodiazepines on a daily basis. The doses of BZDs were significantly higher in non-responders (p=0.007). ROC analysis distinguished responders from non-responders by a criterion of >8mg of diazepam equivalent dose (DZ equi) with a sensitivity of 80% and a specificity of 85% (p˂0.001). RM-ANOVA revealed a different time pattern of response to ketamine between the BZD+ (>8mg of DZ equi) and BZD- (≤8mg of DZ equi) groups, with a significantly worse outcome in BZD+ on day 3 (p=0.04) and day 7 (p=0.02). The results of the study indicate that concomitant benzodiazepine treatment in higher doses may attenuate ketamine’s antidepressant effect. The pathophysiological, clinical and methodological implications of this finding should be considered in future research and ketamine treatment.